Structure activity relationship studies on chemically non-reactive glycine sulfonamide inhibitors of diacylglycerol lipase. Issue 7 (1st April 2016) - Chupak, Louis S.; Zheng, Xiaofan; Hu, Shuanghua; Huang, Yazhong; Ding, Min; Lewis, Martin A.; Westphal, Ryan S.; Blat, Yuval; McClure, Andrea; Gentles, Robert G.
Graphical abstract: Abstract: N -Benzylic-substituted glycine sulfonamides that reversibly inhibit diacylglycerol (DAG) lipases are reported. Detailed herein are the structure activity relationships, profiling characteristics and physico-chemical properties for the first reported series of DAG lipase (DAGL) inhibitors that function without covalent attachment to the enzyme. Highly potent examples are presented that represent valuable tool compounds for studying DAGL inhibition and constitute important leads for future medicinal chemistry efforts.